CHARACTERISTICS OF PATIENTS WITH BRAIN INJURY DUE TO LAND TRAFFIC ACCIDENTS TREATED AT NINH BINH PROVINCIAL GENERAL HOSPITAL IN 2018 (Vietnam Journal of Community Medicine, 2021)
This was an epidemiological study through a retrospective review of 215 medical records of patients with brain injury due to land traffic accidents treated at Ninh Binh Provincial General Hospital. Theresults showed that the majority of research subjects were male, accounting for 80.5%; The age group with higher prevalence of accidents was under 30 years old, accounting for 31.2%; The agegroup of 50-59 years old was at lower prevalence of accidents accounting for 15.8%. The time of the higher chance of occurring accident was between 4p.m and 11p.m daily. The majorityof traffic accidents occurred when riding motorbikes and electric bicycles (82.3%). About 75.0% of the victims received first aid with a gauze bandage; 5.4% of them had broken bones fixed. Amongthe brain injuries, 34.4% of the victims suffered from frontal trauma; 29.3% had unilateral cerebral hemisphere injury, 24.2% had temporal region injury, 15.8% had occipital region injury, and 8.4% ofvictims had parietal injury. More than half of the study subjects (53.5%) were hospitalized for 7-10 days. The rate of patients who have been discharged from the hospital with improved symptoms was81.4%; and 14.9% of patients were transferred to higher level hospitals.
Keywords: Brain injury, traffic accident, land, general hospital, Ninh Binh